Rhodosporidium toruloides cultivated in NaCl‐enriched glucose‐based media: Adaptation dynamics and lipid production. Issue 3 (11th May 2016) - Tchakouteu, Sidoine Sadjeu; Kopsahelis, Nikolaos; Chatzifragkou, Afroditi; Kalantzi, Ourania; Stoforos, Nikolaos G.; Koutinas, Apostolis A.; Aggelis, George; Papanikolaou, Seraphim
Abstract : In the present report and for the first time in the international literature, the impact of the addition of NaCl upon growth and lipid production on the oleaginous yeast Rhodosporidium toruloides was studied. Moreover, equally for first time, lipid production by R. toruloides was performed under nonaseptic conditions. Therefore, the potentiality of R. toruloides DSM 4444 to produce lipid in media containing several initial concentrations of NaCl with glucose employed as carbon source was studied. Preliminary batch‐flask trials with increasing amounts of NaCl revealed the tolerance of the strain against NaCl content up to 6.0% w/v. However, 4.0% w/v of NaCl stimulated lipid accumulation for this strain, by enhancing lipid production up to 71.3% w/w per dry cell weight. The same amount of NaCl was employed in pasteurized batch‐flask cultures in order to investigate the role of the salt as bacterial inhibiting agent. The combination of NaCl and high glucose concentrations was found to satisfactorily suppress bacterial contamination of R. toruloides cultures under these conditions. Batch‐bioreactor trials of the yeast in the same media with high glucose content (up to 150 g/L) resulted in satisfactory substrate assimilation, with almost linear kinetic profile for lipid production, regardless of the initial glucose concentration imposed. Finally, fed‐batch bioreactor cultures led to the production of 37.2 g/L of biomass, accompanied by 64.5% w/w of lipid yield. Lipid yield per unit of glucose consumed received the very satisfactory value of 0.21 g/g, a value among the highest ones in the literature. The yeast lipid produced contained mainly oleic acid and to lesser extent palmitic and stearic acids, thus constituting a perfect starting material for "second generation" biodiesel.